(untitled) (Bangladesh Medical Journal, 2019)
Acute myeloid leukaemia (AML) is treatable and potentially curable disease. Significant morbidity is related to the prolonged, severe neutropenia resulting from the disease as well as the intensive chemotherapy. The administration of granulocyte - colony stimulating factor (G-CSF) is recommended to reduce the neutropenic period. But the current information and guidelines are insufficient about the most appropriate time to start G-CSF and the optimum duration of treatment after chemotherapy in consolidation phase. This study explores better timing to start G-CSF after completion of chemotherapy in consolidation phase of AML patient. This prospective study was conducted in the department of Haematology, Bangabandhu Sheikh Mujib Medical University among AML patients, who received consolidation chemotherapy (high dose cytarabine). Samples were grouped into two arms. Arm-A (Absolute Neutrophil Count >1000/cmm) received prophylactic G-CSF and Arm-B (Absolute Neutrophil Count <1000/cmm) received G-CSF during neutropenia. Filgrastim was used as G-CSF and daily 300 micrograms were given subcutaneously according to study protocol. Statistical analysis was done by parametric (t test) test and appropriate using computer based SPSS (21) Program. Total sample was 19, out of which 6 in prophylactic G-CSF group (Arm-A) and 13 in delayed G-CSF group (Arm-B). Most of the patients were male (63.16%), male to female ratio 1.7:1 and mean age of sample 35 years. Mean ANC at the 1st day of G-CSF application in Arm-A 1170.5/cmm & in Arm-B 272.6/cmm (p=<0.001); mean requirements of G-CSF accordingly 11.5 and 5.9 (p=0.0014), mean 1st day of G-CSF application 9.5th day and 14.5th day (p=0.001). Outcomes in Arm-A and Arm-B were accordingly, mean duration of ANC recovery 10 and 9.85 days (p=0.913), febrile neutropenia 2.67 and 2.57 days (p=0.961), hospital stay 20 and 20.3 days (p=0.259), red cell concentrate transfusion 1.83 and 1.46 units (p=0.550), platelets concentrate transfusion 11.83 and 7.77 bags (p=0.2405), and there was no death case in two arms. Differences of timing to start G-CSF and its requirements between two groups were significant, but the outcomes did not show any statistically significant difference. Bangladesh Med J. 2018 May; 47 (2): 23-28